2021
DOI: 10.1002/hyp.14072
|View full text |Cite
|
Sign up to set email alerts
|

Describing alpine lake influence on stream network temperatures: A statistical modelling approach

Abstract: Systematic variations in atmospheric heat exchange, surface residence time, and groundwater influx across montane stream networks commonly produce an increasing stream temperature trend with decreasing elevation. However, complex stream temperature profiles that differ from this common longitudinal trend also exist,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Previous studies have examined the distinct thermal characteristics of lake‐headed stream temperatures (Dripps & Granger, 2013; Garrett, 2010; Leach et al, 2021; Mellina et al, 2002) and the thermal effects of lakes within lake‐stream networks (Carlson & Poole, 2021). This study presents an example of an indirectly lake‐headed stream, where the interaction of groundwater and lake water, and the hydraulic gradient determine the resulting stream temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the distinct thermal characteristics of lake‐headed stream temperatures (Dripps & Granger, 2013; Garrett, 2010; Leach et al, 2021; Mellina et al, 2002) and the thermal effects of lakes within lake‐stream networks (Carlson & Poole, 2021). This study presents an example of an indirectly lake‐headed stream, where the interaction of groundwater and lake water, and the hydraulic gradient determine the resulting stream temperature.…”
Section: Discussionmentioning
confidence: 99%
“…As lake storage capacity is being filled, the lake influence on downstream temperature will be minimal, but once the storage capacity thresholds are exceeded and lake outflows are initiated, the potential for a persistent downstream lake effect is high. If lake outlet and hillslope temperatures are similar during certain periods, the downstream thermal influence will be negligible regardless of the discharge contributions (Carlson & Poole, 2021). In our summer‐autumn study, the lake had a well‐developed thermal stratification, resulting in persistent outflow of warm water.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that lake influences on downstream temperatures vary in time and diminish with distance downstream due to the increasing influence of hillslope tributary contributions and surface energy exchanges. Generalizing to other lake‐influenced streams, this downstream persistence should vary as a function of lake characteristics (surface area, volume, and residence time), magnitude and distribution of hillslope contributing areas and associated lateral inputs, groundwater and surface water connectivity, and location and size of tributaries (Carlson & Poole, 2021; Leach & Laudon, 2019). Although our study focused on one lake‐stream system, other studies from northern regions have documented downstream cooling patterns below lakes during summer and autumn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations